Creating Access to Land Grant Resources for Multicultural and Disadvantaged Farmers - Marcia Ostrom; Bee Cha; Malaquías Flores (Journal of Agriculture, Food Systems, and Community Development, 2016)
The fastest growing demographic sectors of Washington agriculture are Latino, Asian, and women farmers. The majority of these farms are small, with over three-fourths of Latino, Hmong, or women-operated farms having fewer than 50 acres and less than $50,000 in sales. Small farms make up 90 percent of all Washington farms, with 35,269 counted in the last census. Unfortunately, most conventional farming education models are not well-suited to farmers with limited access to land, water, and capital, or with limited literacy or limited English proficiency. Meeting the needs of this new generation of farmers will require rethinking many standard approaches to public agricultural research, education, and assistance. This article examines various alternative formats for reaching diverse producers with sustainable farming education that have been piloted by the Washington State University Small Farms Program, including participatory courses, farmer-to-farmer learning strategies, experiential workshops, audiovisual strategies, and simultaneous translation.